(untitled) (Third Sector Social Economic Review, 2025)
The purpose of the research is to measure the impact of safety climate on organizational identification and employee performance. The study investigates how the organizational climate in the workplace is perceived by employees and the effect of this perception on organizational identification and employee performance. For this purpose, the literature was reviewed, hypotheses were created and tested based on the collected data. The negative climate perception and inability to identifying himself with the organization can create job dissatisfaction and lack of motivation on the employee and the performance can be adversely affected. In this study, relational survey model was used to measure the effect of security climate perception on teachers’ organizational identification and performance. The data were obtained by evaluating 400 questionnaires that were sent to teachers, selected by convenience sampling method, working in public and private education institutions in Ankara. As a result, a remarkable relationship was found between security climate, organizational identification and employee performance. The severity of the relationship between security climate and identification is 0.619, and the severity of the relationship between security climate and performance is 0.203. The security climate had a 38% effect on organizational identification and a effect on employee performance.